CAG regimen for refractory or relapsed adult T‐cell acute lymphoblastic leukemia: A retrospective, multicenter, cohort study. (3rd June 2020) - Qian, Jie‐Jing; Hu, Xiaoxia; Wang, Ying; Zhang, Yi; Du, Juan; Yang, Min; Tong, Hongyan; Qian, Wen‐Bin; Wei, Juying; Yu, Wenjun; Lou, Yin‐Jun; Mao, Liping; et al.
Abstract: Adult patients with relapsed or refractory T‐cell acute lymphoblastic leukemia (R/R‐T‐ALL) have extremely poor prognosis, representing an urgent unmet medical need. Finding an optimal salvage regimen to bridge transplantation is a priority. The CAG (cytarabine, aclarubicin, and G‐CSF) regimen was initially used by one group in China, showing unexpectedly promising results in 11 R/R‐T‐ALL patients. Here, we report the multicenter results of 41 patients who received the CAG regimen as salvage therapy. After one cycle of the CAG regimen, complete remission and partial remission were achieved in 33 (80.5%) and two (4.9%) patients, respectively. Failure to respond was observed in six patients (14.6%). Early T‐cell precursor (ETP) (n = 26) and non‐ETP (n = 15) patients had a similar CR rate (80.8% vs 80.0%, P = .95). Among 41 patients, allo‐HSCT was successfully performed in 27 (66%) patients (22 in CR and 5 in non‐CR). With a median follow‐up time of 12 months, the estimated 2‐year overall survival and event‐free survival were 68.8% (95% CI, 47.3%‐83.0%) and 56.5% (95% CI, 37.1%‐71.9%), respectively. The CAG regimen was well‐tolerated, and no early death occurred. Our multicenter results show that the CAG regimen is highly effective and safe, representing a novel choice for adult patients with R/R‐T‐ALL and providing a better bridge to transplantation. Abstract : Adult patients with relapsed or refractory T‐cell acute lymphoblastic leukemia (R/R‐T‐ALL) have limited therapeutic options and extremely poor prognosis (CR rate <50% and long‐term survival <20%), which represents an urgent and unmet medical need. Finding an optimal salvage regimen that has a good response and is well‐tolerated to bridge to transplantation is a priority.